Use Of Bauxite Residues For The Rehabilitation Of Abandoned Surface Mines - D. Boufounos (Society for Mining, Metallurgy & Exploration, 2005)
The large open pit areas of surface mining as well as the huge quantities of residues generated during the digestion of bauxite with sodium hydroxide solution to produce alumina are considered as the most important environmental problems associated with the exploitation of bauxites. Aluminum of Greece, which is the only aluminum refinery in the country, located in Agios Nicolaos, Paralia Distomou, Viotia, produces almost 680.000 tones of bauxite residue annually which is pumped through pipes from the refinery to the sea bed of Antikira gulf. In order to avoid any kind of environmental problems related to this disposal method and to reduce the total volume of bauxite residue disposed of in the environment, Aluminium of Greece investigates several alternatives for bauxite residue utilization. In this framework, it also examines the potential use of bauxite residues as a filler in abandoned mining open pits. Bauxite residues are mainly composed of fine particles of silica, aluminum, iron, calcium and titanium oxides and hydroxides. Furthermore, the material presents low hydraulic conductivity, slightly higher than the limit posed for low permeability layers by the EC landfill directive. Based on these properties the dry disposal method was selected for disposing bauxite residues in mining open pits since it has many advantages such as reduced overall disposal cost, effective use of land and minimum environmental impacts. The results obtained for this method, which is investigated at demonstration scale, are presented in this paper.